Strategi Pemasaran Dalam Menghadapi Perubahan Sikap Konsumen Pada Pasca Pandemi Covid-19 - Mufid, Muhammad Munif; Salma Qurrotuain; Selnistia Hidayani (Jurnal Intelek Insan Cendikia, 2024)
A pandemic is a type of epidemic that can affect a large number of people and occurs in any country or region. Coronavirus disease is a respiratory tract infection caused by a virus and is found in Wuhan City, China. In connection with the COVID-19 force majeure condition which has created a trend of independent production, both for self-consumption and for resale. The author is interested in researching marketing strategies in dealing with changes in consumer behavior after COVD-19. This study aims to analyze the perception and changes in the behavior of end consumers and business consumers as well as the strategies taken with the COVID-19 pandemic conditions. Marketing strategy consists of interrelated indicators which include: Market Segmentation, Target Market, Pricing, Promotion and Place. Marketing strategies use 7p, namely; product, price, place, promotion, people, process, and pysical evidence. The rapid economic development in Indonesia has made competition between businesses even tighter. The Covid-19 pandemic has an impact on MSME entrepreneurs which can be reviewed from the perspective of supply and demand.